Sol-gel derived alumina-hydroxyapatite-tricalcium phosphate porous composite powders - OKTAR, FAİK NÜZHET (ELSEVIER SCI LTD, 2012)
In this study, alumina-hydroxyapatite-tricalcium phosphate (alpha-Al2O3-HA-TCP) porous composite powders were produced and characterized. At first, boehmite sol (AlOOH) was obtained via sol gel process by using aluminium isopropoxide (Al(OC3H7)(3)) as the starting material. Bovine hydroxyapatite (BHA) powders derived from deproteinized bovine bones were added as 10, 20, 30 and 50% weight of the starting material to each boehmite sol. Also Na-alginate was added to the boehmite sol as the dispersive agent. Subsequently, gelation for 3 h at 110 degrees C was applied to each sol mixture. Finally, gelated samples were heat treated for 2 h at 500, 800, 1000 and 1300 degrees C. DTA-TGA, XRD, FTIR and SEM-EDS analyses were used to characterize the obtained composite powders composed of alpha-Al2O3-HA-TCP phases. In order to investigate porosity properties, powders were pressed with hydraulic manual press and formed into pellets. Later these pellets were sintered for 2 h at 1300 degrees C. Apparent porosity and bulk density tests were applied to the pellets. The evaluation of these tests results indicate that a novel alpha-Al2O3-HA-TCP composite material with similar to 38-44% apparent porosity has been produced. Crown Copyright (C) 2011 Published by Elsevier Ltd and Techna Group S.r.l. All rights reserved.
Keywords: Sol-gel processes; Composites; Al2O3; Hydroxyapatite; MECHANICAL-PROPERTIES; BIOCERAMICS